Exploring Juvenile Delinquency from the Perspective of Routine Activity Theory in Criminology - Danru Wang (Studies in Law and Justice, 2023)
Juvenile Delinquency has always been a significant proportion of criminal cases in China, and despite a series of policies aimed at curbing it, the effect has been minimal. The types of juvenile delinquency are mainly violent and predatory, and they involve certain contact or connection between the offender and the victim. This is in line with routine activity theory in criminology, which can be used to prevent victimization and reduce adolescent crime. However, before applying the theory, it is necessary to analyze the essential factors of adolescent crime from this perspective. This paper is based on this analysis.